Physical Properties of Fine and Medium Fiber Cotton Cellulose - Sadiyevich, Kosimov Asroriddin; Isoqovich, Tursunov Alisher; Olim qizi, Sabirova Gulnoza (European Journal of Life Safety and Stability (2660-9630), 2021)
Fine-grained cotton cellulose was dissolved in the copper complex [Cu (NN3) 4] (OH) 2 copper-ammonia, which was produced in this way. The fine-fiber cellulose solution was made in a customized circular test tube with a capacity of 500 ml, in which 1 g of fine cotton cellulose samples cut into sizes ranging from 2 g to 4 mm were dissolved in 100 ml copper-ammonia complex. The melting process was sped up by boosting the temperature to 60 degrees Celsius and mechanically mixing the materials continuously. Filtration regulates the melting dynamics of cellulose fibers and their transformation to a totally soluble state.